Welfare and Production Performance of Broilers Reared at Different Stocking Densities - AL Pinheiro; AG Mascarenhas; MB Café; HHC Mello; JCB Lopes; DMLC Rezende (Brazilian Journal of Poultry Science)
ABSTRACT This experiment was conducted to evaluate the welfare and production performance of broilers reared under different stocking densities. A total of 1242 one-day-old Cobb500 broiler males were distributed randomly among four treatments with nine replicates each. The treatments consisted of different broiler stocking densities (10.41; 11.45; 12.50 and 13.54 birds/m²). The parameters evaluated were regadring production performance (body weight, body weight gain, feed intake, feed conversion ratio, uniformity, and carcass yield), animal welfare (cortisol, lactate, total protein, albumin, glucose, triglycerides, cholesterol, uric acid seric, and hemogram), and litter quality (temperature, humidity, and volatilized ammonia concentration). The broilers reared at 12.5 birds/m2 presented the best feed conversion ratio at 42 days of age. Neither the carcass traits nor the stress parameters studied were influenced by the stocking densities. It was concluded that the stocking density of 12.50 birds/m² results in the best feed conversion ratio among the studied treatments for the production cycle of 42 days.